Atypical Kawasaki Disease Complicated With Coronary Artery Aneurysm: A Case Report and Review of Literature - Tanti, Sanjay K (Cureus, 2021)
Background: Kawasaki disease (KD) is an acute, febrile systemic vasculitis of early childhood. A small group of KD patients does not meet the classical presentation of KD, termed incomplete KD. Incomplete or atypical KD patients are usually infants and older children. Because of atypical manifestations of KD, timely diagnosis of KD is difficult, which leads to coronary artery complication Case presentation: We report the case of a nine-year-old boy who developed fever and right side parotitis with painful cervical lymphadenopathy leading to torticollis as the first symptom of Kawasaki disease (KD). A series of investigations revealed elevated inflammatory markers and aneurysmal dilation of coronary artery on echocardiogram, and thus he was diagnosed with atypical KD. Intravenous immunoglobulin was given and the child responded well. Coronary artery aneurysm resolved by six months. Conclusion: A high index of suspicion should be maintained in children presenting with fever and unusual manifestations like lymphadenopathy and parotitis, especially where empiric antibiotics were ineffective. Evaluation of cardiac function and coronary artery status with echocardiography is helpful in defining the diagnosis of KD in such cases. As it is a noninvasive test, it should be undertaken at the first possible clinical suspicion.